Exploring factors influencing the adoption of cloud accounting systems in Indonesian Micro Small and Medium Enterprises: a unified theory of acceptance and use of technology based analysis / Devi Permatasari, Nor Farizal Mohammed and Nur Aima Shafie - Permatasari, Devi; Mohammed, Nor Farizal; Shafie, Nur Aima (Accounting Research Institute (ARI), Universiti Teknologi MARA, Shah Alam, 2024)
In the era of Industry 4.0, rapid technological advancements necessitate Micro, Small, and Medium Enterprises (MSMEs) to navigate these changes for business growth adeptly. Cloud accounting technology emerges as a pivotal tool in this context. Employing the Unified Theory of Acceptance and Use of Technology (UTAUT), this study explored factors influencing MSMEs’ intent to adopt cloud accounting, encompassing performance expectancy, effort expectancy, social influence, facilitating conditions, price value, and perceived security. The study employed a quantitative approach, utilizing survey questionnaires distributed among Indonesian MSME owners. Findings revealed that performance expectancy, effort expectancy, and facilitating conditions significantly influenced their intent to use cloud accounting. Contrastingly, social influence, perceived security, and price value insignificantly impacted MSME owners’ intent to adopt cloud accounting. Furthermore, the study established a positive relationship between MSME owners’ intention to use cloud accounting systems and their actual usage. This actual usage, in turn, positively affected the decision quality of MSME owners. Consequently, the research supported the idea that using cloud accounting systems in small businesses helps them make better decisions about their future, even if some factors did not affect their intentions. This premise shows how internal and external factors are connected within the UTAUT framework.